Entrepreneurship for modern business - Camposano, Jorge A. (Mandaluyong City, Philippines : National Book Store, 2006)
This book includes the valuable contributions of the students, colleagues, friends and co-entrepreneurs whose insights I have gleaned during our professional conversations.